Nursing-home-acquired pneumonia in Germany: an 8-year prospective multicentre study. Issue 2 (5th November 2011) - Ewig, Santiago; Klapdor, Benjamin; Pletz, Mathias W; Rohde, Gernot; Schütte, Hartwig; Schaberg, Tom; Bauer, Torsten T; Welte, Tobias; ,
Abstract : Objective: To determine differences in aetiologies, initial antimicrobial treatment choices and outcomes in patients with nursing-home-acquired pneumonia (NHAP) compared with patients with community-acquired pneumonia (CAP), which is a controversial issue. Methods: Data from the prospective multicentre Competence Network for Community-acquired pneumonia (CAPNETZ) database were analysed for hospitalised patients aged ≥65 years with CAP or NHAP. Potential differences in baseline characteristics, comorbidities, physical examination findings, severity at presentation, initial laboratory investigations, blood gases, microbial investigations, aetiologies, antimicrobial treatment and outcomes were determined between the two groups. Results: Patients with NHAP presented with more severe pneumonia as assessed by CRB-65 (confusion, respiratory rate, blood pressure, 65 years and older) score than patients with CAP but received the same frequency of mechanical ventilation and less antimicrobial combination treatment. There were no clinically relevant differences in aetiology, with Streptococcus pneumoniae the most important pathogen in both groups, and potential multidrug-resistant pathogens were very rare (<5%). Only Staphylococcus aureus was more frequent in the NHAP group (n=12, 2.3% of the total population, 3.1% of those with microbial sampling compared with 0.7% and 0.8% in the CAP group, respectively). Short-term and long-term mortality in the NHAP group was higher than in the CAP group for patients aged ≥65 years (26.6% vs 7.2% and 43.8% vs 14.6%, respectively). However, there was no association between excess mortality and potential multidrug-resistant pathogens. Conclusions: Excess mortality in patients with NHAP cannot be attributed to a different microbial pattern but appears to result from increased comorbidities, and consequently, pneumonia is frequently considered and managed as a terminal event.